A novel approach to peritonitis - Tshepang A. Motsepe (Journal of the Colleges of Medicine of South Africa, 2026)
Peritonitis is a deadly abdominal condition seen across many surgical disciplines, with causes including appendicitis, perforated peptic ulcers, and abdominal trauma. In the South African context, peritonitis is largely influenced by tuberculosis (TB), human immunodeficiency virus (HIV), and widespread malnutrition linked to socioeconomic challenges. Although peritonitis is traditionally classified into primary, secondary, and tertiary types, the addition of quaternary peritonitis could reflect the severe complication risks associated with recalcitrant, systemic, or locally advanced disease. This enhanced grading system, tailored to the local setting, may assist clinicians to accurately assess the severity of peritonitis, improve risk stratification, optimise resource allocation, and ultimately lead to better patient outcomes.